Left ventricular function at similar heart rates during tachycardia induced by exercise and atrial pacing: an echocardiographic study. Issue 2 (February 1987) - Piérard, L A; Serruys, P W; Roelandt, J; Meltzer, R S
Abstract : M mode echocardiography was used in 10 normal subjects to study left ventricular dimension and function variables at identical heart rates during tachycardia induced by supine bicycle exercise or atrial pacing. Echocardiographic data were analysed independently by two observers. The maximum heart rate reached during atrial pacing was lower (mean (1SD) 148 (17) beats/min) than that reached during exercise (mean (1SD) 167 (14) beats/min). The left ventricular end diastolic dimension was greater before supine exercise than before atrial pacing, probably as a result of leg raising. At each graded exercise step the end diastolic dimension remained greater than during atrial pacing and the differences became progressively greater with increasing heart rates. The left ventricular end systolic dimension was not significantly different at each step during the two stresses. During recovery the end systolic dimension was significantly smaller after exercise than at corresponding heart rates induced by atrial pacing. Left ventricular function indices--fractional shortening and peak rates of left ventricular systolic and diastolic dimensional change--were significantly higher during exercise than during atrial pacing and the differences increased with heart rate. It is concluded that the intervention used to change heart rate has an important effect on M mode echocardiographic left ventricular dimensions; indices of left ventricular performance increase progressively during exercise and differ from those measured at the same heart rate during atrial pacing; it is important to consider heart rate, stroke volume, and loading conditions when reference values are used and when the effects of a particular stress are to be interpreted.